Poor early relapse recovery affects onset of progressive disease course in multiple sclerosis - Novotna, Martina; Paz Soldán, M Mateo; Abou Zeid, Nuhad; Kale, Nilufer; Tutuncu, Melih; Crusan, Daniel J; Atkinson, Elizabeth J; Siva, Aksel; Keegan, B Mark; Pirko, Istvan; Pittock, Sean J; Lucchinetti, Claudia F; et al. (Neurology, 2015)
OBJECTIVE: To evaluate the relationship between early relapse recovery and onset of progressive multiple sclerosis (MS). METHODS: We studied a population-based cohort (105 patients with relapsing-remitting MS, 86 with bout-onset progressive MS) and a clinic-based cohort (415 patients with bout-onset progressive MS), excluding patients with primary progressive MS. Bout-onset progressive MS includes patients with single-attack progressive and secondary progressive MS. "Good recovery" (as opposed to "poor recovery") was assigned if the peak deficit of the relapse improved completely or almost completely (patient-reported and examination-confirmed outcome measured ≥6 months post relapse). Impact of initial relapse recovery and first 5-year average relapse recovery on cumulative incidence of progressive MS was studied accounting for patients yet to develop progressive MS in the population-based cohort (Kaplan-Meier analyses). Impact of initial relapse recovery on time to progressive MS onset was also studied in the clinic-based cohort with already-established progressive MS (t test). RESULTS: In the population-based cohort, 153 patients (80.1%) had on average good recovery from first 5-year relapses, whereas 30 patients (15.7%) had on average poor recovery. Half of the good recoverers developed progressive MS by 30.2 years after MS onset, whereas half of the poor recoverers developed progressive MS by 8.3 years after MS onset (p = 0.001). In the clinic-based cohort, good recovery from the first relapse alone was also associated with a delay in progressive disease onset (p < 0.001). A brainstem, cerebellar, or spinal cord syndrome (p = 0.001) or a fulminant relapse (p < 0.0001) was associated with a poor recovery from the initial relapse. CONCLUSIONS: Patients with MS with poor recovery from early relapses will develop progressive disease course earlier than those with good recovery.
Keywords: Female; lidé středního věku; roztroušená skleróza; progrese nemoci; mužské pohlaví; Recurrence; Remission, Spontaneous; Humans; dospělí; časové faktory; Multiple Sclerosis; Multiple Sclerosis, Chronic Progressive; lidé; Middle Aged; Time Factors; Multiple Sclerosis, Relapsing-Remitting; spontánní remise; ženské pohlaví; recidiva; Age of Onset; Disease Progression; chronicko-progresivní roztroušená skleróza; relabující-remitující roztroušená skleróza; Adult; Male; věk při počátku nemoci